Analysis of hydraulic conductivity of tropical peat soil on sand and clay substratum in Pesisir Selatan, West Sumatra - Adrinal, .; Naspendra, Zuldadan; Gusmini, .; Kasim, Susilawati; Jamarun, Novesar; Sisca, Vivi (Rasayan Journal of Chemistry, 2024)
The study of hydraulic conductivity is essential for the effective management of peat drainage systems, particularly in West Sumatra, Indonesia, where peatlands are layered with sand and clay substratum. These substrate variations are believed to influence soil conductivity, indirectly impacting plant growth. This study aimed to compare saturated hydraulic conductivity between peat soils with sand and clay substratum, analyze the characteristics of peat pores affecting conductivity, and establish relationships between soil parameters and peat drainage in both systems. Conducted in Pesisir Selatan, West Sumatra, the study involved 12 observation points for soil hydraulic conductivity. Results indicated that peat soil with a sand substratum exhibited an average hydraulic conductivity (HC) of 1.13 x 10- 3 cm.s-1, five times faster than peat with a clay substratum (2.21 x 10-4 cm.s-1). Interestingly, soil HC values did not correlate with pore characteristics in the peat layer but were significantly associated with those in the substratum layer. Specifically, substratum layer HC positively correlated with Aeration Pores (AP) (r=0.680) and Drainage Pores (DP) (r=0.031), and negatively correlated with Available Water Pores (AWP) (r=-0.817, p<0.047, r2=0.667). Notably, AWP in the sand substratum layer was lower (22.50%vol) than in the clay substratum layer (30.53%vol). Therefore, precise regulation of peat drainage in a sand substratum is crucial to mitigate the potential increase in water levels in peatlands.